Methods of Implementing Kulliyatul Mu’allimin Al-Islamiyah Disciplinary Character Education For Sixth Grade Students at Darussalam Gontor Modern Islamic Institution - Imam Bahroni; Muammar ansori (At-Ta'dib, 2019)
Darussalam Gontor Islamic Institution or often called Gontor is one of the Islamic boarding school educational institutions in Indonesia. Has an important role in the development of education and teaching in Indonesia even in South East Asia. Islamic boarding schools are educational institutions originating from, managed by, and acting for the community. In the context of Darussalam Gontor Islamic Institution, it means that the educational process involves the students as subjects rather than objects of education. They educate themselves through various activities, creativity, and social interactions that are extremely important for the formation of their soul and character. This process is deliberately pursued because in the education at Islamic boarding school which is community oriented with an educational environment the students are prepared to become members of a community that has an independent soul. The purpose of this study is to find out: methods of forming character education for sixth grade students of KMI at Darussalam Gontor Islamic Institution, implementation of the formation of character education forming for sixth grade students of KMI at Darussalam Gontor Islamic Institution, and problems faced in implementing the forming of character education for sixth grade students of KMI Darussalam Gontor Islamic Institution.